Matrix metalloproteinases in tissue remodelling and inflammation - Lagente, Vincent; Boichot, Elisabeth (PIR (Series), 2008)
Matrix metalloproteinases (MMPs) are proteolytic enzymes believed to be involved in many physiological and pathological processes associated with inflammatory reactions. This volume presents advances in the involvement of MMPs in various diseases associated with inflammatory processes.